PENDIDIKAN KARAKTER DALAM PEMBENTUKAN SPIRITUAL QUOTIENT MAHASISWA STIKES DI KOTA PALOPO - Tn. Lubis; Abdullah Sappe Ampin Maja (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
The purpose of this research was to know the form and implementation of character education, and to analyze the process of spiritual formation of student quotient through the concept of character education on health sciences college students in Palopo.This research uses descriptive qualitative research with psycho-individual approach of cultural, institutional, psychological, and pedagogical. Techniques in data collection using observation, interviews, and documentation. The data analysis was done by reducing data, display data, data verivications, and provides conclusions.The form and implementation of character education in STIKES Palopo were: a) Internalization of character values in each learning peoses; b) Integration of character values in each subject contained in the GBPP, syllabus, semester program, and annual program; c) Enabling religious extracurricular activities such as praying in congregation, study or religious dialogue, and commemoration of religious big days (Islam) and the process of establishing spiritual quotient through the concept of character education education are: a) Integration of values character and spiritual values of learning activities; b) Establishment of religious activities within the school; c) Exemplary demonstrated by the Lecturers; and d) Evaluation done by the campus.Implementation of the program of the formation of spiritual quotient and internalization of the values of the characters in the process of teaching and learning in the classroom, then created STIKes students who have a spiritual quotient good by understanding and carrying out the values of the character, so that in everyday life was reflected life of Islamic, respect for parents and lecturers, courteous in speech, polite in acting, always greeting when met, and active in following the process of teaching and learning in the classroom. Key Word: Education Character, Spiritual Quotient Forming, Student